Dominant and Modifiable Risk Factors for Dementia in Sub-Saharan Africa: A Systematic Review and Meta-Analysis - Ojagbemi, Akin; Okekunle, Akinkunmi Paul; Babatunde, Opeyemi (Frontiers in Neurology, 2021)
Sub-Saharan Africa (SSA) is projected to have a rapid increase in the number of people living with dementia by 2050. Yet, there is currently no robust evidence on the risk factors for dementia in the sub-region that could inform context specific interventions. Methods: We conducted a systematic review and meta-analysis of observational studies to determine the dominant and modifiable risk factors for dementia in SSA. We searched MEDLINE, EMBASE, PsychINFO, and African Journals Online using keywords for dementia and Alzheimer’s disease as well as the .mp operator for all 47 SSA countries or regions. We included peer-reviewed original studies with epidemiological designs, conducted random effect meta-analysis and determined the dominant and modifiable risk factors for dementia using the inverse of variance method. Results: A total of 44 studies out of 2848 met criteria for syntheses. The pooled annual incidence of dementia from 8,320 cohort risk years was 2.0% [(95% Confidence Interval (CI)=1.0%-4.0%)]. The pooled prevalence was 5.0% (95% CI=2.0%-7.0%). Older age was the dominant risk factor for both prevalent [(Standard error (S.E=0.3, weight=25.2%)] and incident dementia (S.E=0.02, weight=95.8%), while low educational attainment (S.E=0.19, weight=32.6%) and low cognitive reserve at baseline (S.E=0.2, weight=20.5%) were the best ranked modifiable risk factor for incident dementia. Conclusion: low formal educational attainment which, in SSA, may represent a stable index of low socioeconomic position and health disadvantage over the life course, was the most prominent modifiable risk factor for incident dementia. Findings have implications for deliberate policies, in SSA, to improve access to education across the life course.